International Legal Analysis of the Crime of Aggression under the Rome Statute - Mariska Juliana; Arifin Faqih Gunawan; Wijayono Hadi Sukrisno (PT. Anagata Sembagi Education, 2026)
The crime of aggression is one of the most serious international crimes because it threatens global peace and security. This crime occurs when a state uses armed force against another state in violation of international law. To address this issue, the international community, through the Rome Statute, recognizes aggression as one of the crimes under the jurisdiction of the International Criminal Court (ICC). This article aims to analyze the regulation of the crime of aggression under the Rome Statute and the role of the ICC in prosecuting perpetrators of aggression. The study employs a normative legal research method using statutory and literature approaches. The findings indicate that the regulation of aggression in the Rome Statute represents an important step toward maintaining international peace and ensuring legal accountability for unlawful acts of aggression.